Disease free survival and overall survival from Holliday Junction Recognition Protein (HJURP) expression in non-metastatic breast cancer patients - Harahap, Wirsma Arif; Oktavenra, Ari; Rustam, Rony; Rafli, Rhandyka; Hardisman, Hardisman (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Holliday Junction Recognition Protein (HJURP) is a gene that integrates with Centromere Protein A (CENPA) which plays a role in cell proliferation. It is related to radiation response where high HJURP level give a good response to radiotherapy and a high rate of apoptosis. It is a prognostic factor for Disease Free Survival (DFS) and Overall Survival (OS) and a predictive biomarker on radiotherapy. This study aimed to analyze the correlation between HJURP expression with DFS and OS in breast cancer patients who received radiotherapy. Methods: This study used a quantitative method with a cross-sectional design. Data were collected from 57 non-metastatic breast cancer patients undergoing radiotherapy from 2019 to 2021. Patients were examined from paraffin blocks by IHC examination using HJURP antibodies which were then assessed for expression. Data were analyzed using survival analysis with Kaplan-Meier and Cox Regression test. Results: The majority of breast cancer patients who received radiotherapy had positive HJURP expression (68.4%). There was no statistically significant correlation between HJURP expression with DFS or OS in breast cancer patients who received radiotherapy. However, there was a statistically significant correlation between radiotherapy interruptions and OS where patients with interruptions >3 times had a risk of death 8.40 times faster than patients with interruptions ≤3 times (95% confidence interval [CI]). Conclusions: Although HJURP expression was not related with survival in breast cancer patients who received radiotherapy, it is a good candidate as a predictive biomarker of radiotherapy response.